3(2+s)=36

Simple and best practice solution for 3(2+s)=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2+s)=36 equation:


Simplifying
3(2 + s) = 36
(2 * 3 + s * 3) = 36
(6 + 3s) = 36

Solving
6 + 3s = 36

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 3s = 36 + -6

Combine like terms: 6 + -6 = 0
0 + 3s = 36 + -6
3s = 36 + -6

Combine like terms: 36 + -6 = 30
3s = 30

Divide each side by '3'.
s = 10

Simplifying
s = 10

See similar equations:

| -8x-7x=-60 | | g(x)=6x-5 | | 21+7/2r=-21 | | 21+7/2=-21 | | f(x)=9x-1 | | -(7-7n)-(6n-4)=n+1+n | | x-(-4)=4 | | 6.7+1.3n=3.19 | | -4(8-m)=-4(1-8m) | | 2.5x+7.5=32.5 | | 0=6x^2+10x+2 | | 11x+27=5x+33 | | 4p-6p=2(8p-3)-8(5p+2) | | 2(7+b)=42 | | Y=ln(x+1)+4 | | 3(7+B)=90 | | -7(1+2m)=-5(2m-5) | | 5/3/4/5+3/2x2/3 | | 13x+21=4x+12 | | -5a-6(1-5a)=2-(2a+8) | | x^2-2x+12=3x+36 | | -36x^2+144x-60=0 | | (m-15)(m+9)=m-15 | | -(5+3p)-6p=-4(p+2)-7 | | (y-8)(y+2)=y-8 | | 0.4/a=0.32 | | 7x-8=3x-40 | | 3a+(a+b)=180 | | a+3a+(a+b)=180 | | 1.5(x-1)-1.5=2.5(x-3) | | -8(4n+8)-2(1-3n)=-n+8+n+4 | | -2+2(6)= |

Equations solver categories